Degradation and Mineralization of Pesticide Isoprocarb by Electro Fenton Process - Hayet Bakhti; Najib Ben Hamida; Didier Hauchard (The Journal of Pure and Applied Chemistry Research, 2020)
Electro Fenton with volumic cathode consisting of granules of carbon graphite was applied to degrade the insecticide Isoprocarb in aqueous solutions. The effects of various factors including current intensity and pesticide initial concentration were investigated in order to obtain the best experimental conditions for its degradation and mineralization. Kinetic studies determined that the insecticide removal followed a pseudo first order. The absolute rate constant for the oxidation of Isoprocarb by hydroxyl radicals were determined as 3.32 × 109 L mol−1 s−1 by competitive kinetics method taking benzoic acid as reference compound. In this work, we have also studied the mineralization of aqueous solutions of this insecticide in term of total organic carbon (TOC). After 3 hours of electrolysis, and at I = 800 mA, more than 40 % of the organic carbon presented in the solution is mineralized. Various aromatic by-products, principally formed by oxidation of the pesticide, accompanied by hydroxylation of the aromatic cycle, have been identified. Thus, the oxidative opening of the aromatic ring leads to the formation of carboxylic acids and nitrate ions. The biodegradability of Isoprocarb is estimated by the measurement of its Biochemical Oxygen Demand (BOD5).Keywords: Isoprocarb, electro Fenton, mineralization, hydroxyl radicals, oxidation.